Islamic Republic of Iran : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper on Iran focuses on the Targeted Subsidy Reform Law (TSRL). This is the basic law governing the implementation of the subsidy reform in Iran. The TSRL envisaged bringing subsidized prices close to international levels over a five-year period. The paper reviews the implementation of the first phase of the subsidy reform, with a particular emphasis on macroeconomic management. The sharp depreciation of the exchange rate and high inflation significantly undermined progress under the reform. High inflation partially reversed the relative price change under the reform.